2018
DOI: 10.1016/j.ccell.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Functional Annotation of Somatic Mutations in Cancer

Abstract: The functional impact of the vast majority of cancer somatic mutations remains unknown, representing a critical knowledge gap for implementing precision oncology. Here, we report the development of a moderate-throughput functional genomic platform consisting of efficient mutant generation, sensitive viability assays using two growth factor-dependent cell models, and functional proteomic profiling of signaling effects for select aberrations. We apply the platform to annotate >1,000 genomic aberrations, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
226
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(243 citation statements)
references
References 42 publications
10
226
0
Order By: Relevance
“…To identify SNVs with a high probability of protumorigenic function in tumor development or maintenance, we focused on known activating/oncogenic alterations as well as deleterious mutations. The interpretation of the oncogenic and deleterious character of the SNV mutations was based on publicly available databases (eg, OncoKB, ClinVar [National Center for Biotechnology Information, National Library of Medicine, National Institutes of Health, Bethesda, MD]) and on published research results, as detailed in Table 1 . Activating mutations were identified in 14 genes, most of which were oncogenes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify SNVs with a high probability of protumorigenic function in tumor development or maintenance, we focused on known activating/oncogenic alterations as well as deleterious mutations. The interpretation of the oncogenic and deleterious character of the SNV mutations was based on publicly available databases (eg, OncoKB, ClinVar [National Center for Biotechnology Information, National Library of Medicine, National Institutes of Health, Bethesda, MD]) and on published research results, as detailed in Table 1 . Activating mutations were identified in 14 genes, most of which were oncogenes.…”
Section: Resultsmentioning
confidence: 99%
“… Interpretation of the activating/oncogenic mutations is based on information from OncoKB, ClinVar, or www.cancerhotspots.org (as of 09/18), with the exception of BRAF‐K499N, for which this information was derived from Ng et al All alterations are predicted to be oncogenic or likely oncogenic. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies identified I767M as a gain‐of‐function mutation with transformative potential, resulting in increased HER2 kinase activity and sustained AKT phosphorylation . However, another study demonstrated no difference in cell proliferation or viability of HER2 I767M compared to wild‐type HER2 . HER2 mutations have been well studied in breast cancer, including HER2 nonamplified breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 However, another study demonstrated no difference in cell proliferation or viability of HER2 I767M compared to wild-type HER2. 21 HER2 mutations have been well studied in breast cancer, including HER2 nonamplified breast cancer. 22,23 However, the diagnostic utility of uncovering a kinase mutation in HER2 is unknown.…”
Section: Case Reportmentioning
confidence: 99%